Educational Policies and Legislation in China - Xu, Xiaozhou (Springer Singapore, 2018)
This book provides a comprehensive overview of the development of educational policies and legislation in China, particularly following the introduction of Reform and Opening Up in 1978. The scope of this book: (1) provides the theoretical basis and framework of educational policies; (2) explains key educational laws and legislation; and (3) introduces readers to policies for educational internationalization, private education, lifelong learning and teacher education. The book is intended for researchers, teachers and graduate students in the field of comparative education, educational policy and legislation, educational management. Readers will find essential information on the most important educational laws and legislation, as well as the recent characteristics of and trends in educational policies in China.